Characterization and antioxidant properties of Manchurian walnut meal hydrolysates after calcium chelation. (August 2020) - Fang, Shunxiang; Ruan, Guorui; Hao, Jing; Regenstein, Joe M.; Wang, Fengjun
Abstract: A Manchurian walnut protein hydrolysates-calcium (MWPH-Ca) was prepared its characteristics and antioxidant activities after in vitro simulated gastrointestinal digestion were investigated. The optimal conditions for the chelation reaction were peptide to calcium ratio of 3:1, pH of 8, chelation time of 40 min, and chelation temperature of 45 °C, and the final chelation rate was 67.2%. The peptides were agglomerated after chelation, as the particle size increased. The FTIR results showed that the main sites of chelation are amino nitrogen atoms, carboxyl groups and the CO of the peptide bond which has a negative dipole. The MWPH-Ca generally maintained good solubility in the gastrointestinal environment, which could improve the calcium absorption. In addition, the MWPH-Ca still retained antioxidant activity and was stronger than that of the MWPH after simulated digestion. Highlights: Calcium-binding peptide from Juglans mandshurica was prepared using alcalase. The chelating conditions were optimized using response surface methodology. The characterizations of peptide before and after calcium chelation were compared. Peptide-Ca chelate retained antioxidant activity after gastrointestinal digestion.